COVID-19 and Inequality : How Unequal Was the Recovery from the Initial Shock? - Agrawal, Sarthak; Cojocaru, Alexandru; Montalva, Veronica; Narayan, Ambar; Bundervoet, Tom; Ten, Andrey (World Bank, Washington, DC, 2021)
The restrictions on mobility and economic activity that were put in place to mitigate the health impacts of the COVID-19 (coronavirus) pandemic have had an unequal impact both across and within countries, with vulnerable populations within developing countries being affected disproportionately. An important concern is that the recovery may be similarly inequitable. Across the 17 developing countries in our sample, where policies became more conducive to mobility and economic activity, we indeed observe a partial recovery of employment and incomes in most countries, as well as improvements in food security. Although job recovery and lower policy stringency were accompanied by an overall fall in the share of the food-insecure population from 13 percent to 9 percent, those living in rural areas witnessed slower declines in food insecurity. However, the recovery was not only incomplete, but also uneven within countries. In particular, the recovery in employment among those who suffered larger initial shocks - - women, non-college-educated, and urban workers - - was not sufficient to significantly reduce the initial disparities in losses. By August-September, female employment had only recovered 30 percent of what was lost between pre-pandemic and May-June (versus 49 percent for men). Finally, more recent data for a smaller number of countries up to January 2021 indicates that while food security continued improving in these countries, recovery in employment appears to have stalled, while the disparities by gender and education persisted.